ITC study on the interaction of some bile salts with tragacanth, Arabic, and guar gums with potential cholesterol-lowering ability - Massa, Michele; Compari, Carlotta; Fisicaro, Emilia (Frontiers in Nutrition, 2023)
The urge to design new safe and natural functional foods for blood lipid control has grown especially after the coming into effect of the recent EU Commission regulation 2022/860, which regulates the consumption of "red yeast rice" (RYR), made by fermentation of rice with Monascus purpureus. RYR is perceived as a natural functional food but poses health risks for frail consumers. The results of the present work form part of our systematic study on the binding ability of some soluble dietary fibers (SDF) from different natural sources towards selected bile salts (BS). We use isothermal titration calorimetry (ITC) with the idea to shed light on the mechanism, if any, through which they might exhibit cholesterol-lowering activity. Epidemiological studies are sometimes conflicting and provide only hypotheses about the mechanism of action, the most accredited being the reduction of reabsorption of BS in the gut. Previous measurements on negatively charged pectin and positively charged chitosan, revealed specific binding interaction with monomer NaDC for pectin and strong exothermic interactions with NaTC and NaTDC for chitosan at pH=3. In this study, we examined two plant exudates (Arabic gum and tragacanth gum) and guar gum, extracted from guar beans, and their interaction with the same bile salts. ITC measurements do not evidence specific interactions between gums and the studied BS. This suggests that if these gums possess cholesterol-lowering ability, they likely operate via a different mechanism most probably related to a viscosity increase. Moreover, the addition of NaC, the most abundant BS in the bile, at a very low concentration (below the cmc) induces a structural change in the solution. These results support the hypothesis that the cholesterol-lowering activity may be related to the increase in viscosity of the guar solution favored by NaC, the major component of the bile.